Питомі трудомісткості обслуговування легкових автомобілів фірмовими СТО - Павлюк, В. І. (НТУ "ХПІ", 2015)
Проаналізовано нормативи трудомісткостей технічного обслуговування і ремонту легкових автомобілів, що обслуговуються фірмовими станціями технічного обслуговування автомобілів. Розглянуті норми трудовитрат ТО і ремонту для різних модифікацій легкових автомобілів світових виробників. Використовуючи методи теорії ймовірності і математичної статистики для обробки даних, визначені орієнтовні величини питомих трудомісткостей технічного обслуговування і ремонту легкових автомобілів.

This issue has analysed the standarts of labour input in maintenance and repair of passengers cars according to warranty period. The data of service stations belongs to car manufacturers. The labour input in maintenance and repair is being studied for cars of different world vehicle manufacturers. The methods of Probability Theory and Mathematical Statistics have been used for data processing. The logarithmic–normal Law of Distribution of random Variable has been identified. The numeral characteristics of Law of Distribution of random Variable have been determined. The calculated value of labour input in maintenance and repair of passengers cars has been defined. The labour input in maintenance and repair of passengers cars is given for different car classes. The determined labour input in maintenance of passengers cars of Asian manufacturers is larger than similar of Europian manufacturers. The received values of l abour input are lower than the defined ones in the legal normative documents in our country. The results of these calculations can be used in constructing Service Stations which belong to Vehicle manufacturers or Brand Service Station.
The specific labour input in maintenance of passengers cars by Brand Service Stations
Keywords: технічне обслуговування; ремонт; випадкова величина; specific labour input; maintenance; repair; vehicle service stations; passenger car